2018
DOI: 10.3892/etm.2018.6099
|View full text |Cite
|
Sign up to set email alerts
|

A novel dressing seeded with embryonic artery CD133+ cells and loaded with the Sirt1 agonist SRT1720 accelerates the healing of diabetic ischemic ulcers

Abstract: Refractory ischemic ulcers that occur in patients with diabetes present a major clinical challenge. Embryonic artery cluster of differentiation 133+ cells (EACCs) may promote the healing of diabetic ulcers; however, the high glucose environment in the diabetic ulcers decreases the survival rate of transplanted EACCs and inhibit their biological function. Furthermore, microcirculation in diabetic ischemic ulcers is impaired, which inhibits the beneficial effect of EACCs. In the current study, the Sirt1 agonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Among class IIb HDACs, HDAC6 has been revealed to be an agonist of glucocorticoids and endorse glucocorticoid-induced hepatic gluconeogenesis [45]. Also, HDAC6 can endorse glucoseprovoked ROS (reactive oxygen species) generation by regulating acetylation of peroxiredoxin-1 (Pdrx1) and thioredoxin-1 (Trx-1) [46].…”
Section: Hdacs and Dmmentioning
confidence: 99%
See 1 more Smart Citation
“…Among class IIb HDACs, HDAC6 has been revealed to be an agonist of glucocorticoids and endorse glucocorticoid-induced hepatic gluconeogenesis [45]. Also, HDAC6 can endorse glucoseprovoked ROS (reactive oxygen species) generation by regulating acetylation of peroxiredoxin-1 (Pdrx1) and thioredoxin-1 (Trx-1) [46].…”
Section: Hdacs and Dmmentioning
confidence: 99%
“…Deletion of HDAC9 in a hyperglycemic state has been reported to improve glucose tolerance in mice [123]. HDAC6 has been regarded as an essential modifier of glucocorticoid-induced hepatic gluconeogenesis and impair glucose metabolism by regulating nuclear translocation of the glucocorticoid receptor [45]. Thus, inhibition of class II HDACs has been shown to ameliorate insulin resistance and glucose intolerance.…”
Section: Role Of Hdacs In Glucose Homeostasismentioning
confidence: 99%
“…Of 5844 screened studies, a total of 7 were included (online supplementary figure 1). [14][15][16][17][18][19][20]…”
Section: Study Selectionmentioning
confidence: 99%
“…Diabetes was present as a comorbidity in 322 wounds (Ischemia=161; Non-ischemia=161) during assessments performed at days 7 (n=144), 14 (n=136) and 21 (n=42). All included studies reported wound area at days 7 and 14, [14][15][16][17][18][19][20] whereas four studies reported wound area at day 21. 14 16-18 All time-points were eligible for meta-analysis.…”
Section: Effect Of Ischemia On Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation